PENGARUH CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI - Bagas Dwi Purnomo; Irmawati Irmawati (JURNAL LENTERA BISNIS, 2024)
This study aims to analyze Brand Image and Brand Trust on Consumer Loyalty and Consumer Satisfaction as Mediating Variables. The population of this study were students of Universitas Muhammadiyah Surakarta who used Asus laptops. The sample size of this study was 75 respondents. Data collection using a questionnaire. The analysis method used is path regression analysis and Smart PLs analysis tools with Outer model stages (validity and reliability), and Inner Model (Goodness of Fit, Path Coefficient, Indirect Effect). The results of this study are Brand Image and Trust have a significant positive effect on customer satisfaction. Brand Image and Trust have a significant positive effect on consumer loyalty Consumer Satisfaction has a significant positive effect on consumer loyalty. Customer satisfaction mediates significantly positively between brand image and customer loyalty. Satisfaction mediates significantly positively between brand trust and consumer loyalty. Keywords: Brand Image, Brand Trust, Consumer Loyalty, Consumer Satisfaction